1992
DOI: 10.1042/bj2830893
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the amplification reactions of blood coagulation by site-specific inhibitors of α-thrombin

Abstract: Hirudin and hirulog-1 [D-Phe-Pro-Arg-Pro-[Gly]4-desulphohirudin-(54-65)] abrogate the enzyme activities of alpha-thrombin by binding the enzyme simultaneously at its catalytic centre and fibrin(ogen)-recognition exosite. In contrast, hirugen [hirudin-(54-65)] binds alpha-thrombin solely at the fibrin(ogen)-recognition exosite, and competitively inhibits fibrinopeptide A release. To investigate the extent to which the fibrin(ogen)-recognition exosite is involved when alpha-thrombin catalyses the amplification r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…It is im portant that clinically developed drugs are compared sys tematically side by side in the same systems, since only then do the differences in their action become apparent. Such limited studies have been previously reported, [1][2][3] but comparisons between several different thrombin in hibitors (as opposed to comparisons between structural analogues of the same agent) are lacking. Protease gener ation inhibition assays using biochemically defined sys tems provide a useful profile on the modulatory actions of newer antithrombin agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is im portant that clinically developed drugs are compared sys tematically side by side in the same systems, since only then do the differences in their action become apparent. Such limited studies have been previously reported, [1][2][3] but comparisons between several different thrombin in hibitors (as opposed to comparisons between structural analogues of the same agent) are lacking. Protease gener ation inhibition assays using biochemically defined sys tems provide a useful profile on the modulatory actions of newer antithrombin agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of thrombin in catalyzing the conversion of fibrinogen to fibrin has been established, more information about thrombin's role in feedback am plification loops in the coagulation cascade is becoming available. [1][2][3][4] Until recently only limited information was available on the feedback regulatory actions of formed thrombin.…”
mentioning
confidence: 99%
“…Other authors have already reported in detail on the biochemical and bio logical properties of both substances [2,7,11], In a series of in vitro and in vivo test systems the superiority of both inhibitors over heparins was demonstrated [ 13,[27][28][29]. However, there are only few comparative studies of rhi rudin and this analogue [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…This bivalent inhibitor has been termed 'hirulog-1' by Maraganore et al [11]. Few comparative studies of rhirudin and its analogues have as yet been carried out [12][13][14], We examined both anti coagulants in vitro and in animal models. The results demonstrate marked differences be tween the two compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Some patents on lepirudin argatroban and bivalirudin were reported [90][91][92][93][94][95][96][97]. Three parenteral DTI are currently approved for use in the United States: lepirudin [90,98], argatroban [91][92][93]99], and bivalirudin [95,100]. Ximelagatran and dabigatran are oral DTI that are being investigated for the prevention and treatment of TED.…”
Section: Direct Thrombin Inhibitorsmentioning
confidence: 99%